AKLIMATISASI BENUR UDANG WINDU (Penaeus Monodon) SEBAGAI UPAYA BUDIDAYA DI LUAR LINGKUNGAN HIDUPNYA: SEBUAH KASUS DI KABUPATEN LAMONGAN - Maryadi, Maryadi (BPPT)
Penaeus monodon or tiger prawn is the most prominent farmed crustacean product in international trade and has driven a signifi cant expansion in aquaculture in many developing countries in Asia. Market prices during its early development were quite good due to little competition and strong demand from the international markets, mainly Japanese market. Culture technology in inland areas has been improved using a very minimal amount of seawater (only 2-3ppt) and closed systems to prevent salinization offreshwater resources. The model of culturing commercial tiger prawn on minimal amount of seawater in Lamongan Regency was applied since 1987.Key words : benur udang windu, Peneaeus Monodon